Association of vitamin and/or nutritional supplements with fall among patients with diabetes: A prospective study based on ACCORD and UK Biobank - He, Lingfang; Ma, Tianqi; Zhang, Guogang; Cheng, Xunjie; Bai, Yongping (Frontiers in Nutrition, 2023)
Aims: To assess the associations of vitamin and/or nutritional supplements (VNS) with falls among patients with diabetes. Methods: 9,141 and 21,489 middle-aged participants with diabetes from Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial and UK Biobank were included. Use of VNS was collected at baseline, and fall events were recorded using annual questionnaires in ACCORD and electric records in UK Biobank during follow-up. The associations of VNS use with fall risk were analyzed using logistic regression models in ACCORD and Fine-Gray sub-distribution hazard models in UK Biobank. The role of specific supplements was also estimated in UK Biobank, adjusting for confounding factors and multiple comparisons. Results: 45.9% (4193/9141, 5.5 median follow-up years) patients in ACCORD and 10.5% (2251/21489, 11.9 median follow-up years) in UK Biobank experienced fall and in-patient events during follow-up, respectively. In ACCORD, VNS using was associated with an increased risk of fall (full-adjusted odds ratio [OR]: 1.26, P<0.05). In UK Biobank, despite no significant association between VNS overall and in-patient fall, vitamin B, calcium, and iron using increased the risk of falls significantly (full-adjusted hazard ratio range: 1.31-1.37, P<0.05). Conclusions: Use of specific VNS increased the risk of fall among patients with diabetes. The non-indicative use of nutritional supplements for patients with diabetes might be inadvisable.